Advancing knowledge of electrochemically generated lithium microstructure and performance decay of lithium ion battery by synchrotron X-ray tomography. (July 2019) - Sun, Fu; He, Xin; Jiang, Xiaoyu; Osenberg, Markus; Li, Jie; Zhou, Dong; Dong, Kang; Hilger, André; Zhu, Xiaoming; Gao, Rui; Liu, Xiangfeng; Huang, Kai; et al.
Graphical abstract: Abstract: An intrinsic knowledge gap between current understandings obtained experimentally and the underlying working or degradation mechanisms of rechargeable lithium batteries still remains, giving direct rise to application challenges, e.g., safety issues, predicaments in identifying performance-aging factors and dilemmas in guiding further research directions. Against this background, non-destructive and three-dimensional (synchrotron) X-ray tomography that guarantees a direct visual access to inner electrodes has been employed herein to: in-situ record the evolution of internal short circuits; characterize the behaviors of widely employed separators; investigate the morphological evolution of Li electrodes under different cycling conditions; and study the degradation mechanisms of Li/carbon cells. By incorporating the currently presented results with the previously published studies on those topics, a complete picture of the degradation mechanism of rechargeable lithium batteries has been painted. This advancement of mechanistic understanding supplies the missing pieces of information to bridge fundamental R&D research activities and practical applications.